Protein Consumption In Communities Affected By Stunting In Daerah istimewa Yogyakarta - Puspitaningrum, Dwi Aulia; Hikmah, Khoirul; Azimatun Nur, Muhammad Maulana; Putra, Aditya Ananta; Trijuna, Ravid Ikhsan; Hidayadi, Mukminan Arif; Defiana, Vista Nur (Agro Ekonomi, 2023)
Inadequate protein consumption is characterized by a low intake of energy and proteinous foods, leading to stunted growth and negative public health outcomes. Therefore, this study aims to determine the factors influencing consumer behavior in purchasing animal and vegetable proteinous foods in Daerah Istimewa Yogyakarta (DIY), as well as to analyze the relationship between protein consumption and these influentialfactors. A quantitative design was used along with a survey approach, involving both primary and secondary data. The study participants were selected using a non-probability sampling method. Data were collected through observations, interviews, literature studies, and documentations. Multiple linear regression analysis, including covariate tests, was then used for analysis. The results of the research showed that household income, the income of women, the number of family members, the number of children under the age of five, the age of women, and the distance from the house to the nearest shop/minimarket had a significant impact on protein consumption among households with stunted children in DIY. Furthermore, Gunung Kidul, Kulon Progo, and Sleman districts had protein consumption of <1 million Indonesian Rupiah (IDR), while Bantul Regency and Yogyakarta Municipality were >1 million IDR.